The use of click chemistry in sphingolipid research - Jamecna, Denisa; Höglinger, Doris (Journal of cell science, 2024)
Sphingolipid dysregulation is involved in a range of rare and fatal diseases as well as common pathologies including cancer, infectious diseases or neurodegeneration. Gaining insights into how sphingolipids are involved in these diseases would contribute much to our understanding of human physiology, as well as the pathology mechanisms. However, scientific progress is hampered by a lack of suitable tools that can be used in intact systems. To overcome this, efforts have turned to engineering modified lipids with small clickable tags and to harnessing the power of click chemistry to localize and follow these minimally modified lipid probes in cells. We hope to inspire the readers of this Review to consider applying existing click chemistry tools for their own aspects of sphingolipid research. To this end, we focus here on different biological applications of clickable lipids, mainly to follow metabolic conversions, their visualization by confocal or superresolution microscopy or the identification of their protein interaction partners. Finally, we describe recent approaches employing organelle-targeted and clickable lipid probes to accurately follow intracellular sphingolipid transport with organellar precision.
Gesehen am 19.11.2024